2019
DOI: 10.1073/pnas.1912700116
|View full text |Cite
|
Sign up to set email alerts
|

Exquisite sensitivity of adrenocortical carcinomas to induction of ferroptosis

Abstract: Adrenocortical carcinomas (ACCs) are rare and highly malignant cancers associated with poor survival of patients. Currently, mitotane, a nonspecific derivative of the pesticide DDT (1,1-(dichlorobiphenyl)-2,2-dichloroethane), is used as the standard treatment, but its mechanism of action in ACCs remains elusive. Here we demonstrate that the human ACC NCI-H295R cell line is remarkably sensitive to induction of ferroptosis, while mitotane does not induce this iron-dependent mode of regulated necrosis. Supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 52 publications
2
74
0
Order By: Relevance
“…1k) and an increased sensitivity to RSL3 treatment (Fig. 2g), which is in line with a very recently published study 40 . NCI-H295R cells without Se, although more sensitive to RSL3, were still not as sensitive as CU-ACC2 cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1k) and an increased sensitivity to RSL3 treatment (Fig. 2g), which is in line with a very recently published study 40 . NCI-H295R cells without Se, although more sensitive to RSL3, were still not as sensitive as CU-ACC2 cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A study found that significant increases in the expression of GPX4 and sensitivity to ferroptosis in ACCs, suggesting that inducing ferroptosis may be a promising approach for the treatment of ACCs. In addition, ferroptosis inducers may be more effective and less toxic than mitotane in treating ACC patients 50 .…”
Section: Adrenocortical Carcinomas (Accs)mentioning
confidence: 99%
“…The bmMSC control group displayed no green fluorescence (Figure 2A), suggesting no LPO accumulation. Similar to the control group, the positive control group (ferrostatin-1) [63,64] also showed negligible green fluorescence ( Figure 2C). This result indicates that LPO accumulation is effectively inhibited by ferrostatin-1-a widely used ferroptosis-inhibitor-by targeting LPO [10,63,64].…”
Section: Resultsmentioning
confidence: 65%